Feminist legal theory - Eichner, Maxine; Huntington, Clare (Studies in law, politics, and society, 2016)
This volume carefully examines the relationship between gender, equality, and power across an array of realms: sex, reproduction, pleasure, work, money. It identifies social, political, economic, developmental, and psychological and somatic forces, operating both internally and externally, that complicate the expression and constraint of power.